2023
DOI: 10.3390/nu15194148
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Inflammatory Diet Is Correlated with High Veillonella rogosae, Gut Inflammation and Clinical Relapse of Inflammatory Bowel Disease

Ilanna Marques Gomes da Rocha,
Raquel Torrinhas,
Danielle Fonseca
et al.

Abstract: Inflammatory bowel diseases (IBD) are chronic conditions arising from an intricate interplay of genetics and environmental factors, and are associated with gut dysbiosis, inflammation, and gut permeability. In this study, we investigated whether the inflammatory potential of the diet is associated with the gut microbiota profile, inflammation, and permeability in forty patients with IBD in clinical remission. The dietary inflammatory index (DII) score was used to assess the inflammatory potential of the diet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Recently, it was reported that senolytic drugs have anti-inflammatory effects in zebrafish models of chronic skin inflammation and in a high-cholesterol diet [174][175][176][177][178][179]. Taken together, these characteristics suggest that rag mutant zebrafish offer a valuable platform for investigating and seeking treatments for senescence in vivo, as well as for the aging process induced by chronic inflammation (Figure 3).…”
Section: Senescencementioning
confidence: 96%
“…Recently, it was reported that senolytic drugs have anti-inflammatory effects in zebrafish models of chronic skin inflammation and in a high-cholesterol diet [174][175][176][177][178][179]. Taken together, these characteristics suggest that rag mutant zebrafish offer a valuable platform for investigating and seeking treatments for senescence in vivo, as well as for the aging process induced by chronic inflammation (Figure 3).…”
Section: Senescencementioning
confidence: 96%
“…The development of dysbiosis, inflammation, and oxidative stress during IBD can be modulated by diet, ∼5 times more closely associated than genetic factors [ 2 , [65] , [66] , [67] ]. High consumption of dietary fat and sugar can increase mucosal dysbiosis, inflammation, and horizontal gene transfer in the microbiome to increase pathogenic colonization such as Pseudomonadota (formerly Proteobacteria) and Bacillota (formerly Firmicutes) phyla [ 68 , 69 ] and decrease SCFA-producing bacteria Roseburia spp., Eubacterium rectale, and Ruminococcus bromii [ 70 , 71 ]. Dysbiosis and damaged intestinal cells promote the influx of ROS and inflammasomes from impaired mitochondria biogenesis [ 72 , 73 ]: the hypoxic epithelial cells and inflammatory cytokines induce mitochondrial leaky electron transfer chain and peroxidase production for oxidative stress [ 74 , 75 ], which results in inadequate energy production and tiredness [ 75 ].…”
Section: Introductionmentioning
confidence: 99%